ANALISA PERFORMANSI RADIO FREQUENCY MODULATION di TARUTUNG SUMATERA UTARA - Febryanto Marthyn Sutrisno Simanjuntak; Sigit Kusmaryanto; Wahju Adi Prijono (Jurnal Mahasiswa TEUB, 2022)
The development of technology, especially in the field of wireless communication, has developed quitte rapidly. Software Defined Radio (SDR) technology is one of the births of wireless communication technology which is a new challenge for communication engineers. The development of SDR systems has made significant progress in recent years because these systems have the ability to improve the quality of previous analog radio communications and can be used as a replacement for hardware implementations. SDR can be used when redesigning a radio software system where later the parameters can be changed to get the desired quality using the existing codes. To be able to solve code and process radio signals required hardware such as computers to support SDR technology. An application that runs inside GNU Radio by construct block. So the purpose of this thesis is to determine the frequency allocation of FM radio stations that are used in an area at the same time. The design of the spectrum analyzer in this thesis is based on SDR using an RTL-SDR type 2832U dongle. This spectrum research used RTL-SDR, suggested improvements such as the need for an increase in the RTL-SDR specifications used in this thesis, need to do research and design using other SDR and it is necessary to add facilities by setting the resolution bandwidth to determine the level of some radio signals.Index Terms – RTL-SDR, GNU Radio, Spectrum Analyzer